Effects of mulberry leaf extract on the intestinal health of spotted sea bass (Lateolabrax maculatus) - Zhou, Sishun; Huang, Zhangfan; Lin, Hao; Kong, Lumin; Ma, Jianrong; Long, Zhongying; Qin, Huihui; Liu, Longhui; Lin, Yi; Li, Zhongbao (Frontiers in Marine Science, 2023)
Mulberry leaf extract (ELM) has the functions of promoting growth, antioxidant, improving intestinal microbial composition, which can improve intestinal function and reduce the occurrence of intestinal diseases. A feeding trial was conducted to investigate the effects of ELM on intestinal antioxidant capacity, tissue morphology and microbial diversity of spotted sea bass, Lateolabrax maculatus (initial weight 9.00 ± 0.02 g). Results show, Results show, ELM significantly increased the weight gain rate (WGR), specific growth rate (SGR) and fatness (F) of the spotted sea bass (P<0.05), and promoted the growth of the spotted sea bass. ELM significantly increased intestinal trypsin (TRS) activity (P<0.05), and ELM increased intestinal lipase (TRS) and amylase (AMS) activities (P>0.05), thereby improving intestinal digestion and absorption of nutrients. ELM significantly increased the activity of catalase (CAT) in the intestine (P<0.05), and had a tendency to increase superoxide dismutase (SOD) and glutathione (GSH), while malonaldehyde (MDA) had a tendency to decrease, but had no significant effect (P>0.05). ELM can improve the intestinal morphology of spotted sea bass, significantly increase the length of intestinal villi, thereby increasing the surface area of the intestinal tract, and improving the digestion and absorption of nutrients (P<0.05). Compared with the control group, ELM significantly increased the intestinal microbial ACE, Chao1, and Shannon indexes of the spotted sea bass (P<0.05), and ELM could improve the intestinal microbial composition of the spotted sea bass and increase the abundance of the dominant flora in the spotted sea bass gut. The above results showed that the addition of ELM in the feed could promote the growth of the spotted sea bass, improve the antioxidant capacity of the intestinal tract of the spotted sea bass, and improve the intestinal morphology and microbial composition of the spotted sea bass. The research results provide a theoretical basis for the application of ELM in improving the enteric health of aquatic animals.